2003
DOI: 10.1002/app.12215
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerization kinetics of hyperbranched acrylated aromatic polyester

Abstract: ABSTRACT:The influences of the irradiation temperature, comonomer content, sample thickness, and photoinitiator concentration on the polymerization kinetics of hyperbranched acrylated aromatic polyester (HAAPE) were investigated with photo-differential scanning calorimetry and IR measurements. The maximum photopolymerization rate increased with the temperature rising up to 110°C but decreased beyond 110°C. An activation energy of 16 kJ mol Ϫ1for the photopolymerization was obtained below 110°C from an Arrheniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…The higher conversion of the blend results from the combined synergetic action of increased network mobility and related lower unsaturation concentration compared to DPHA, and reduced viscosity compared to Acrylated Boltorn H20. A similar trend was found for a reactive blend of an acrylated HBP with TMPTA17 and for HBP‐containing epoxy formulations 12…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The higher conversion of the blend results from the combined synergetic action of increased network mobility and related lower unsaturation concentration compared to DPHA, and reduced viscosity compared to Acrylated Boltorn H20. A similar trend was found for a reactive blend of an acrylated HBP with TMPTA17 and for HBP‐containing epoxy formulations 12…”
Section: Resultssupporting
confidence: 75%
“…Cook16 investigated the photopolymerization of bisphenol‐A‐dimethacrylate and found that the final degree of conversion was largely unaffected by variations in the initiation and polymerization rates, but was instead dependent on network mobility and hence on the curing temperature and resin structure. Specifically, Kou et al17 studied the influence of temperature, composition, and photoinitiator concentration on the photopolymerization of a reactive blend of an acrylated hyperbranched polymer with trimethylolpropane triacrylate (TMPTA). For a reactive blend of HBP with 20–60% of TMPTA, they found higher ultimate conversions compared to the pure products, which was attributed to differences in viscosity, unsaturation concentration, and network morphology.…”
Section: Introductionmentioning
confidence: 99%
“…This can be accounted for by a rapid gelation of the recording medium which impedes further diffusion of residual monomers, and undergoes premature vitrification before segregation of the reactants reaches its term. At the end of the recording step, the monomer conversion was measured to be 76, 85 and 64% for intensity of 0.1, 0.4 and 1.0 mW cm À2 , respectively, 19 which corroborates the previous statement.…”
Section: Holographic Diffraction Recordingsupporting
confidence: 88%
“…13 The initiation period shortens with increasing the exposure intensity, even disappears at the exposure intensity of Dendritic polyisophthalate endcapped with naphthyl groups 511 1.0 mW cm À2 . 19 For lower intensity, weaker than 0.4 mW cm À2 , the diffusion rate of monomer MA exceeds its photopolymerization rate. As the photopolymerization proceeds, monomers diffuse from darker regions to brighter ones.…”
Section: Holographic Diffraction Recordingmentioning
confidence: 99%
“…The reactivity of unreacted doubles bonds is determined by the mobility of the polymeric network, which would decrease because of HUA addition. Therefore, the R pmax values of EB600/HUA blends are the result of the competition between the two aforementioned factors 10. Consequently, a broader peak for R p is obtained as a large amount of HUA is added.…”
Section: Resultsmentioning
confidence: 99%